Exploring the Roles and Influences of Strategy Management Units (SMUs): An Integrative Review - Zenagebriel Dessalgn Abebe; Mehmet Barca (Commercium : Journal of Business and Management, 2026)
The impetus for this review is the gap in the strategic management literature concerning the presence, roles, and influence of Strategy Management Units (SMUs). This review aimed to identify what is known about SMUs, elaborate and synthesize previous findings, identify the theoretical foundation for SMUs, and propose future directions. For this purpose, a step-wise integrative literature review (ILR) is used to assess the existing literature. The framework used in this review is the ADO-TCM (Antecedents-Decisions-outcome and Theories-Context-Methods) approach. Using this approach, it was possible to explicate how theories such as the Resource-Based View could be used to provide explanations in SMU studies. Through a rigorous analysis of extant studies, it was possible to map three central thematic areas of SMU studies, namely: the factors that affect the units’ presence and organization, SMUs roles, and the units’ influence. The review also enabled us to identify the main roles of SMUs, such as overseeing the strategic management process, strategy formulation, business development, and so on. It is proposed that future studies focus on antecedents of SMUs’ presence and roles, the units' impact on several organizational outcomes, as well as the interlink between other related concepts.